(untitled) (Journal of Philosophy Culture and Political Science, 2018)
In this article we consider the main categories of phenomenology of religion – «symbols» and «religious symbols». Studying the concepts of philosophers of different epochs, it was analyzed universality of symbols. Scientific analysis of this issue allowed us to conclude that, the universal symbol was able to meet the needs of religion, culture and civilizations of different periods. The identification of reasons for the formation and basic conditions of the symbol showed that there is a contradiction in the opinions of the philosophers. One group of scientists describes the symbol as a means of cognition of the world and the universal object of culture, another- as an ontological reality destroyed by culture. Analyzing the three main features of the religious symbol, the authors confirmed the relevance of the latter to the needs of religious consciousness. On the basis of the study of the nature of the symbol, we concluded that the symbol makes the beliefs of the believers more accessible to the feelings of the supernatural, gives the «existence» to non-exist religious objects, masks their illusory. Key words: symbol, religious symbol, religious consciousness, religiosity, religious values.